Pengaruh Pengelolaan Kelas terhadap Prestasi Belajar Siswa di MI Al-Karomah - Siti Rosidah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2020)
This research was carried out because the learning outcomes (raport scores) of students must be in accordance with the assessment principles in the Education Unit Level Curriculum (KTSP), which must be in accordance with the size limit with the specified Minimum Completeness Criteria (KKM), because it is the result of an assessment in determining completeness. learning of students, and to achieve the expected achievement, a research was conducted, whether there was an influence of a teacher's ability to manage the class on learning achievement. The research was conducted at MI Al Karomah in the district of West Bogor. The entire research population was used as a research sample called the saturated sample, with a total sample of 25 respondents. The research approach uses quantitative methods. The research instrument uses a questionnaire for classroom management and documentation for student achievement. The results of the questionnaire recapitulation were determined by the validity test of the Pearson product moment formula and the reliability test using Spearman Brown, from 20 valid items, 20 items were valid, because r count > r table and all were reliable. To determine the correlation of variable x (class management) to variable y (learning achievement), using Pearson's product moment formula. From the calculation of Pearson's product moment formula, r count = 0.798 > r table = 0.396, which means it is significant, that class management has an influence on student learning achievement. From the calculated r, it is determined that KD (determinant coefficient) = 0.64% means that the variable x (class management) contributes 64% to the variable y (student learning achievement) the rest is influenced by other factors. From the value of Df = 23 with a significance level of 5%, the value of r table is 0.413. then consulted into the hypothesis formula obtained 0.798 > 0.413 or r arithmetic > r table, meaning Ho is rejected and Ha is accepted.